Geronimo Stilton: The Kingdom of Fantasy #1 (HC) - Stilton, Geronimo (Kingdom of Fantasy, 1., 2009)
Geronimo knew from the start that it was no ordinary day, but he certainly didn't expect to find a golden staircase in my attic. Up at the top, there was a door. And beyond the door was a world he never could have imagined -- the Kingdom of Fantasy!